Four-Point Impedance Changes After Cochlear Implantation for Lateral Wall and Perimodiolar Implants. Issue 10 (December 2022) - Razmovski, Tayla; Bester, Christofer; Collins, Aaron; Tan, Eren; O'Leary, Stephen J.
Abstract : Objective: Monitor four-point impedance in cochlear implant recipients over time and determine if implant type, surgical approach, and electrode positioning affected impedance measurements. Study Design: Prospective observational. Setting: Hospital. Patients: Adult cochlear implant recipients implanted with a perimodiolar or lateral wall cochlear implant. Main Outcome Measure(s): Mean values for four-point impedances were calculated for all electrode contacts at perioperative and 3 months after surgery. Linear mixed models were applied to the impedance data to compare between implant types and time points. The angular insertion depth and electrode position relative to the medial and lateral wall, commonly termed the Intracochlear Position Index (ICPI), were collected and compared with impedance measurements. Results: Perioperatively, the four-point impedance was similar between implant types, with perimodiolar implants having marginally higher impedance values in the basal region. At 3 months after surgery, impedances significantly increased in the basal half of the electrode array for both implants, with higher impedance values for CI532 implants. There were no significant differences in insertion angle depth between implant types. The ICPI values for the seven most basal electrodes were similar for both implants; however, CI532 arrays were significantly more medially placed along the remaining apical portion of the array, which is expected. ICPI values did not correlate with impedance measurements for either implant. Conclusions: Four-point impedance increases at 3 months after surgery may reflect fibrous tissue formation after cochlear implantation. The higher impedance values in perimodiolar implants may reflect a more extensive fibrosis formation as a result of surgical approaches used, requiring drilling of the cochlea bone.